PEDAGOGICAL MECHANISMS OF PHYSICAL EDUCATION EXERCISES IN INCREASING THE SOCIAL ACTIVITY OF SCHOOL GUESTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article contains a systematic description of the main results of the research related to increasing the effectiveness of physical education of schoolchildren based on the organization of an integrated educational environment of physical education and sports, which allows you to combine your efforts. state and public organizations, schools and families create conditions for the well-rounded development of the student's personality, his self-realization in physical education and sports. The concept of humanization of physical education and sports environment was revealed.